2010
DOI: 10.1111/j.1466-8238.2010.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and environmental gradients of lianas and vines in China

Abstract: Aim Climbing plants are characterized by long, wide vessel elements, which may be vulnerable to cold-or drought-induced embolism. However, the difference in vulnerability between lianas (woody climbing plants) and vines (herbaceous climbing plants) has not yet been reported. Here we hypothesize that both lianas and vines are more sensitive to variations in water and temperature than are self-supporting plants.Consequently, the proportions of lianas and vines in flora are expected to decline significantly along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 38 publications
(90 reference statements)
1
39
0
Order By: Relevance
“…Species richness and individual numbers per site were strongly correlated, and the regression analyses recovered very similar suites of environmental variables. The latitudinal decline of species richness and it's relationship to climatic factors parallel the situation in many other plant and animal groups (Wiens et al 2006;Hawkins and De Vries 2009;Hu et al 2010). The causes for this decline are still unknown, and may involve either the carrying capacity of ecosystems as determined by water availability and temperature (Hawkins et al 2003), or historical and evolutionary causes (Wiens and Donoghue 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Species richness and individual numbers per site were strongly correlated, and the regression analyses recovered very similar suites of environmental variables. The latitudinal decline of species richness and it's relationship to climatic factors parallel the situation in many other plant and animal groups (Wiens et al 2006;Hawkins and De Vries 2009;Hu et al 2010). The causes for this decline are still unknown, and may involve either the carrying capacity of ecosystems as determined by water availability and temperature (Hawkins et al 2003), or historical and evolutionary causes (Wiens and Donoghue 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Vines and lianas responded differently to water availability. Lianas are considered to be more vulnerable to drought than vines and other plant forms because the wide and long vessels easily become nonconductive due to drought-induced embolism (Salleo and Lo Gullo 1986;Ewers et al 1990Ewers et al , 1991Hu et al 2010). Although the below ground storage tissues of climbers may help them withstand diurnal drought, these may not be effective during extended drought (Rundel and Franklin 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Hu et al (2010) investigated the changes of lianas and vines along the macro rainfall gradients across China and found that the proportion of lianas in the flora increased significantly with increasing rainfall (100-2,500 mm). In comparison, vine growth remained constant when rainfall exceeded 700 mm, but increased significantly with increasing rainfall when rainfall was less than 700 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations